“THE IMPACT OF CLIMATE CHANGE ON GLACIERS” - Rustamova Adash Eshankulovna; Tuychibayeva Mehribon Bobur qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Climate change has negatively affected various parts of life, including the loss of glaciers. Along with human activities, a huge amount of glaciers are melting due to an increasing temperature and a lack of precipitation. This ongoing glacier retreat not only influences the environment but can also damage the economy in several ways, by reducing natural habitats, limiting water sources, and affecting agriculture and tourism. This article delves into the importance and effects of glacier loss on the ecology and socio-economy, with clear examples, and suggests solutions to slow the pace of melting.